Gold-catalyzed cascade cyclization-oxidative alkynylation of allenoates. - Hopkinson, M; Ross, J; Giuffredi, G; Gee, A; Gouverneur, V (2010)
A gold(I)-catalyzed cascade cyclization-oxidative cross-coupling process has been applied to prepare β-alkynyl-γ-butenolides directly from allenoates and various terminal alkynes. Following an initial gold-catalyzed C-O bond forming allenoate cyclization, a mechanism based on a Au(I)/Au(III) redox cycle has been proposed with Selectfluor acting as the external oxidant.